Identifikasi dan Karakterisasi Golongan Senyawa Metabolit Sekunder Bioaktif pada Ekstrak Kulit Batang Kamboja Bali (Plumeria rubra L.) Berdasarkan Analisis Kromatografi dan Spektrofotometri Uv-Vis - Putri Putri; Suci Rahmadani; Ashaja Syamsi; Aqilah Salsabilah Rusli; Andryani Astuti Anwar; Fani Agusni Mansur (Universitas Muhammadiyah Manado, 2026)
Bali frangipani (Plumeria rubra L.) is a medicinal plant traditionally used in Indonesia and is known to contain various bioactive secondary metabolites. This study aimed to identify and characterize the secondary metabolite compounds present in the ethanol extract of Bali frangipani stem bark through phytochemical screening, fractionation, chromatographic separation, and determination of total flavonoid content. The research employed an experimental laboratory design with a descriptive qualitative approach. Stem bark was extracted by reflux using 96% ethanol, followed by liquid-liquid fractionation, column chromatography, thin-layer chromatography (TLC), preparative TLC, and two-dimensional TLC. Phytochemical screening confirmed the presence of alkaloids and saponins, whereas flavonoids, tannins, and steroids/triterpenoids were not detected in the crude extract. Column chromatography of the ethyl acetate fraction yielded 28 fractions that were combined into five sub-fractions. TLC analysis identified three major spots, and the flavonoid-like compound was successfully isolated as isolate A, exhibiting yellow-green fluorescence under UV 366 nm with an Rf value of 0.30–0.34. Two-dimensional TLC demonstrated a single spot, indicating satisfactory purity. Total flavonoid content, determined using the AlCl₃ colorimetric method with quercetin as the reference standard, was 4.883 mg QE/g extract (4.883%), indicating a relatively low flavonoid level according to the Indonesian Herbal Pharmacopoeia. These findings contribute to understanding the phytochemical profile of Bali frangipani stem bark and support its potential application in pharmaceutical and natural product research.